SUSTAINABLE URBAN FARMING THROUGH HOUSEHOLD WASTE UTILIZATION: A COMMUNITY ENGAGEMENT INITIATIVE IN PKK RW IX GRIYA BHAYANGKARA, SIDOARJO - Ramadhani Mahendra Kusuma; Fitri Wijayanti; Puji Lestari Tarigan; Purnomo Edi Sasongko; Yudi Nur Supriadi (Jurnal Abdimas Bina Bangsa, 2023)
This community engagement initiative focused on promoting sustainable urban farming practices in Balai RW IX Griya Bhayangkara, Sidoarjo, East Java. The program, carried out in collaboration with academic teams from Universitas Pembangunan Nasional "Veteran" East Java (UPNVJT) and Universitas Surabaya (UBAYA), aimed to address the challenges of food security and limited agricultural spaces in urban environments. A total of 63 participants, mainly housewives, took part in the program. The engagement included a comprehensive knowledge-sharing session on the benefits of urban farming, encompassing social and financial advantages, along with various vertical farming techniques and suitable plant selections. Furthermore, participants were introduced to eco-friendly pest and disease control measures utilizing biopesticides. The interactive approach, including question and answer sessions, fostered active engagement and ensured a deeper understanding of urban farming practices. The subsequent hands-on training, utilizing recycled plastic bottles as planting media, provided practical experience in setting up urban farming systems. The program's success highlighted the importance of academic-community collaborations in disseminating accurate and up-to-date knowledge while catering to the specific needs of the target audience. By empowering the community with relevant skills and knowledge, this initiative contributed to enhancing food security, promoting sustainable practices, and strengthening the bond between academia and local communities in fostering resilient food systems and environmental consciousness